Neurodevelopmental Disorders (NDDs) in Children: Role of Maternal Factors - Banu, Laila Areju Man; Haque, FM Anamul; Tasnim, Saria (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Neurodevelopmental disorders (NDDs) are disabilities affecting normal brain development and function. The early stages of brain development are critical, and disruption of this process results in neurodevelopmental disorders (NDDs) in children. Common neurodevelopmental disorders in children include autism spectrum disease (ASD), attention deficit hyperactivity disorder (ADHD), cerebral palsy (CP), intellectual disability (ID), epilepsy, learning disability, schizophrenia etc. Though the causes of NDDs are multifactorial, epidemiological studies have shown that a number of maternal factors such as, diabetes, hypertension, obesity, maternal immune activation, infection, diet, genetics, lifestyle etc. also influence the development of NDDs. In this review, we focus on some common NDDs in children and the mechanism by which different maternal factors may contribute to the development of NDDs. With the increasing incidence of NDDs, it is urgent to mitigate the risk and severity of these conditions through both preventive measures in pregnancy and developing treatment strategies. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 139-147